Cell agglomeration algorithm for coupling microkinetic modeling and steady-state CFD simulations of catalytic reactors. (2nd February 2017) - Rebughini, Stefano; Cuoci, Alberto; Dixon, Anthony G.; Maestri, Matteo
Highlights: Coupling micro-kinetic models with multi-region steady-state CFD simulations. Cell Agglomeration methodology is employed to reduce the computational cost. Detailed assessment of the accuracy and the computational gain is presented. The capabilities are shown with complex geometries and complex micro-kinetic models. Abstract: We propose the application of a Cell Agglomeration (CA) algorithm for coupling detailed microkinetic models with multi-region steady-state Computational Fluid Dynamics (CFD) simulations of catalytic reactors. This numerical methodology – originally developed for dynamic CFD simulation with detailed gas-phase kinetics – is herein applied in the context of steady-state microkinetic CFD simulations of catalytic reactors by exploiting the particular structure of the governing equations of the adsorbed species, which are characterized by the absence of the transport term. The potentialities of the method are assessed by the analysis of different reactor geometries and microkinetic mechanisms in a wide range of operating conditions. Our tests show this method to allow for a reduction of the computational time up to an order of magnitude. Thus, the CA algorithm turns out to be a useful tool to enable the detailed and fundamental simulation of catalytic devices in steady-state conditions.